PENGGUNAAN METODE MIND MAPPING DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI - Suci Rizkiana; Suryo Ediyono (Universitas Negeri Medan, 2019)
Abstract: Use Of Mind Mapping Method In Learning Writing Explanation Text. The purpose of this study was to determine the increase in interest and writing skill of explanation text using mind mapping method in students of Nusawungu State Vocational School. Data sources in this study included: learning events, informants, and documents. Data collection technique through: observation, interviews, tests, and document analysis. Validity test of the data used triangulation techniques and data source methods. Data analysis techniques used in this study were comparative descriptive techniques and critical analysis. The use of mind maping method was proven to increase students' interest in learning to write explanatory texts. The percentage of students' interest in pre-cycle was 52.94%, cycle I was 67.64%, and cycle II was 88.24%. Based on these results it can be concluded that the use of mind mapping methods can improve the process and learning outcomes of students in writing explanatio texts.Keywords : Mind Mapping Method, Learning, Explanatory Text.Abstrak: Penggunaan Metode Mind Mapping Dalam Pembelajaran Menulis Teks Eksplanasi. Tujuan penelitian ini adalah untuk mengetahui peningkatan minat dan keterampilan menulis teks eksplanasi menggunakan metode mind mapping pada siswa kelas XI SMK Negeri Nusawungu. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Subjek penelitian adalah siswa dan guru bahasa Indonesia kelas XI SMK Negeri Nusawungu. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik deskriptif komparatif dan analisis kritis. Persentase minat siswa pada prasiklus sebesar 52,94%, siklus I sebesar 67,64%, dan siklus II sebesar 88,24%. Berdasarkan hasil tersebut dapat disimpulkan bahwa penggunaan metode mind mapping dapat meningkatkan proses dan hasil pembelajaran menulis teks eksplanasi siswa. Kata kunci: Metode Mind Mapping, Pembelajaran, Teks Eksplanasi.